Genetics and the nephron. Issue 2 (25th October 2013) - Marlais, M; Coward, R J
Abstract : There have been phenomenal advances in our understanding of renal biology over the last 20 years through our ability to define the genetic mutations causing kidney disease in children. This review will take you through a trip down the nephron and highlight how these conditions may present to the paediatrician and the molecular basis for their biological effects.